2013
DOI: 10.1016/j.cell.2013.03.022
|View full text |Cite
|
Sign up to set email alerts
|

TNF Dually Mediates Resistance and Susceptibility to Mycobacteria via Mitochondrial Reactive Oxygen Species

Abstract: Summary Tumor Necrosis Factor (TNF) constitutes a critical host defense against tuberculosis but its excess is also implicated in tuberculosis pathogenesis in zebrafish and humans. We elucidate the pathways by which TNF mediates tuberculosis pathogenesis using the zebrafish. TNF excess induces mitochondrial reactive oxygen species (ROS) in infected macrophages through RIP1–RIP3-dependent pathways. While initially increasing macrophage microbicidal activity, ROS rapidly induce programmed necrosis (necroptosis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
540
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 525 publications
(588 citation statements)
references
References 69 publications
17
540
2
4
Order By: Relevance
“…Previously, TNF and IL-17 have been linked to a protective, innate immunity against TB (61,63), and an LTA polymorphism has been associated with susceptibility to the disease (64). The role of Tnfa appears, however, complicated; Roca and Ramakrishnan recently showed that either deficient or excess production of this cytokine accelerates TB pathogenesis through reduced microbicidal activity of macrophages or programmed necrosis of macrophages, respectively (65). Since furinA downregulation causes a proinflammatory phenotype, FurinA deficiency could be beneficial for protection by increasing the early microbicidal activity of innate cells through upregulated Tnfa levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, TNF and IL-17 have been linked to a protective, innate immunity against TB (61,63), and an LTA polymorphism has been associated with susceptibility to the disease (64). The role of Tnfa appears, however, complicated; Roca and Ramakrishnan recently showed that either deficient or excess production of this cytokine accelerates TB pathogenesis through reduced microbicidal activity of macrophages or programmed necrosis of macrophages, respectively (65). Since furinA downregulation causes a proinflammatory phenotype, FurinA deficiency could be beneficial for protection by increasing the early microbicidal activity of innate cells through upregulated Tnfa levels.…”
Section: Discussionmentioning
confidence: 99%
“…Work in the zebrafish larvae has shed light on this issue and has provided evidence that although the early granuloma promotes growth, mycobacterial growth is further enhanced in the extracellular milieu when bacteria are released after macrophage necrosis, or if macrophages are absent altogether (Clay et al 2007(Clay et al , 2008Tobin et al 2010Tobin et al , 2012Ramakrishnan 2012;Roca and Ramakrishnan 2013). Several immune mechanisms have been implicated in necrosis.…”
Section: Exiting the Intracellular Environment Through Macrophage Necmentioning
confidence: 99%
“…1). Excess TNF caused excessive inflammation leading to Receptor-interacting serine/threonine kinase (RIPK) 1-and RIPK3-dependent necrosis of granuloma macrophages via production of mitochondrial reactive oxygen species (ROS) (Tobin et al 2012;Roca and Ramakrishnan 2013). Accordingly, and in stark contrast to TNF-deficiency, macrophages experiencing an excess of TNF signaling initially have enhanced control of intracellular mycobacterial growth because of the ROS.…”
Section: Tnf Excess As a Cause Of Granuloma Necrosismentioning
confidence: 99%
“…Interestingly, the overexpression of LTA4H and subsequent high levels of the leukotriene B4 (LTB4) and low levels of LXA 4 also leads to an increase in host cell programmed necrosis and increased susceptibility to mycobacterial infections (Tobin et al 2012). This is due to the induction of excessive TNF production by LTB4, which keeps bacterial replication low, but favors induction of host cell necrosis and excessive inflammation leading to tissue damage and pathology (Tobin et al 2012;Roca and Ramakrishnan 2013). Hence at both extreme ends of the spectrum, high LXA 4 /no LTB4 and high LTB4/no LXA 4 , the outcomes for the host are very similar with high levels of host cell necrosis, host tissue pathology, and host susceptibility (Tobin et al 2012;Roca and Ramakrishnan 2013).…”
Section: Host Cell Programmed Necrosis and Consequences To Mtb Pathogmentioning
confidence: 99%
“…This is due to the induction of excessive TNF production by LTB4, which keeps bacterial replication low, but favors induction of host cell necrosis and excessive inflammation leading to tissue damage and pathology (Tobin et al 2012;Roca and Ramakrishnan 2013). Hence at both extreme ends of the spectrum, high LXA 4 /no LTB4 and high LTB4/no LXA 4 , the outcomes for the host are very similar with high levels of host cell necrosis, host tissue pathology, and host susceptibility (Tobin et al 2012;Roca and Ramakrishnan 2013). This is despite the fact that the bacterial numbers are quite different in the two scenarios.…”
Section: Host Cell Programmed Necrosis and Consequences To Mtb Pathogmentioning
confidence: 99%